Antimonopoly regulation of the activities of digital companies and the operation of Internet platforms in Russia and in the European Union - V. G. Istomin (Правоприменение)
The subject. The article examines the antimonopoly regulation of relations arising in the course of the activities of modern companies that ensure the operation of certain digital online platforms. The development of digital information technologies has led to the emergence of various new forms of economic and social communications. These forms include, among other things, digital technological platforms operating on the Internet and representing a kind of platform within which information interaction of various subjects takes place, related to the implementation of their professional activities or interpersonal communication. In this regard, the law faces the task of ensuring effective regulation of relations that are formed in the context of the development of electronic market systems and digital services. An important role in this should be assigned to antimonopoly legislation, since the possession of large data sets and the latest information technologies can lead to companies trying to use their resources to violate the rights of other subjects.The aim of the study is to determine the legal essence of the Internet platform and to identify possible features and limits of antimonopoly regulation of the activities of companies that ensure their work, including taking into account the current Russian and foreign legislation and law enforcement practice in this area.Research methods are formal – logical interpretation, systemic method and comparative analysis.The main results, scope of application. Digital technological platform is a complex phenomenon that includes various results of intellectual activity, both subject to and not subject to legal protection, including computer programs, databases, as well as technical means, ensuring the functioning of the digital platform. In addition, the analysis of Russian antitrust legislation and the theory of civil law led to the conclusion that the existing exemptions from the scope of the rules on the prohibition of monopolistic activities established for holders of exclusive intellectual rights could significantly complicate the application of antitrust rules to digital companies that are copyright holders results of intellectual activity that are part of the Internet platform. At the same time, the currently established law enforcement practice actually follows the path of limiting these antimonopoly immunities, despite their legislative consolidation, which is hardly justified. On the other hand, the existence of broad antitrust immunities is also unfounded. In order to bring the antimonopoly legislation in line with the needs of the emerging digitalization relations antitrust immunities are subject to limitations.Conclusions. There are new criteria for determining the dominant position of digital companies in the relevant markets, which include network effects, large user data and significant barriers to entry into the market.